Massive transfusion in obstetric hemorrhage: What are the risk factors and can they be predicted? - Aktemur, Gizem; Çalışkan, Şeyda; Karabay, Gülşan; Yurtçu, Engin; Özbay, Koray; Erdoğan Atalay, Nihan; Saraç, Ömer Doğukan; Ceylan, Yasin; Çelen, Şevki; Soysal, Çağanay (The European Research Journal, 2025)
Objectives: This study aims to identify the risk factors associated with massive transfusion in obstetric hemorrhage and evaluate their predictive value to facilitate early intervention and improve maternal outcomes. Methods: A retrospective cohort study was conducted on 1305 women who received blood transfusions for obstetric hemorrhage at Etlik City Hospital between October 2022 and December 2024. Patients were categorized into two groups: those who required massive transfusion (≥10 units of blood products) and those who received at least one unit of transfusion. Demographic, clinical, obstetric, and hematological parameters were analyzed. Statistical comparisons were performed using chi-square, Fisher's exact, Mann-Whitney U, and independent sample t-tests. Results: A history of recurrent miscarriage, two or more previous cesarean sections, congenital uterine abnormalities, and uterine rupture were significantly associated with massive transfusion (P